ANALISIS TINGKAT KEPUASAN NASABAH PADA AKAD MURABAHAH DI UNIT PENGELOLA KEUANGAN (UPK) MANDIRI SYARIAH SELAKAU - sualdi sualdi (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
This research was conducted to determine whether the variable complain,Ansurace,reliability,Responsivenes,Empathyas well as the level of customer satisfaction towardsthe level of customer satisfaction on murabahah contracts at UPK Mandiri Selakau, Sambas Regency. The method used is (library research). While the form of associative research, which is associative research, is research that aims to find out the influence or relationship between two or more variables. For data analysis this study uses instrument testing, classical assumptions and Simple Linear Regression testing. The results of this study indicate that Complain, Assurance, Reability, Responsivenes do not have a positive but significant effect on customer satisfaction. Meanwhile, at the level of customer satisfaction, it can show the characteristics of products and services so that customers are satisfied or dissatisfied with the services provided. Satisfaction increases if the quality of service provided to customers matches the employee's perceived goals. The factors that determine the level of customer satisfaction are: a. Reliability b. Responsiveness c. guarantee d. Attention / empathy e. Complaint